Optimal Bias Current Design for Visible Light Communications Based on LED Electrical-Thermal Effect - Yu Mu (IEEE, 2021)
In visible light communication (VLC) system, the intensity of light emitting diode (LED) is modulated to transmit data. As a transmitter, the design of LED should consider the performance of lighting and communication simulataneously. However, the output flux of LED is jointly determined by the electrical and thermal characteristics, and is concave-related to the forward bias current. In order to maximize the use of LEDs, in this paper, the mutual restriction of optical, electrical and thermal mechanisms for the LED systems are considered, and a dynamic photoelectrothermal model is established. Then, the optimal bias current is presented according to the electrical-thermal relationship of LED. Modulating LED at this bias current can maximize the communication performance without sacrificing the light flux. Finally, a BER experiment to verify the optimal communication performance is conducted at this bias current.